Konsep Politik Kenegaraan Dalam Islam: Studi Analisis Tentang Pemikiran Politik al-Ghazali - Mursyidi Ridwan (Justicia Islamica, 2005)
This study aims to analyze the concept of state politics in Islam based on the thought of al-Ghazali. The method used is qualitative with a descriptive-analytical approach, through a literature review of al-Ghazali's main works, especially Al-Tibr al-Masbuk and Ihya' Ulum al-Din, as well as other references that discuss his thoughts. The results of the study show that al-Ghazali views politics as an instrument for upholding justice and maintaining social order within the framework of sharia. He emphasizes the importance of a close relationship between religion and the state, where the leader must have moral legitimacy and be responsible for the welfare of the people. This study confirms that al-Ghazali's political thought remains relevant in the discourse of contemporary Islamic politics, especially in the context of leadership based on Islamic ethics and values.